MENUMBUHKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI MELALUI BUKU TEMATIK KELAS RENDAH DI SEKOLAH DASAR / MADRASAH IBTIDAIYAH - Prastowo, Andi (PD PGMI se Indonesia, 2019)
The quality of primary education in Indonesia in the last two decades has not changed much. One of the reasons for this condition is that learning at the elementary school/ madrasah level of madrasah has not yet developed high-level thinking skills. Therefore, starting in 2013, the government changed the primary education curriculum by presenting the 2013 curriculum. One of the substantial changes is that subjects are presented thematically for elementary schools/ madrasah ibtidaiyah. The curriculum change also gave birth to thematic textbooks, no longer subject-based textbooks. This study aims to describe what high-level thinking skills are developed through thematic books for students and how to design learning to grow these thinking skills in thematic books for teachers. This research applies a qualitative approach to the design of library studies. The primary source of this study is a thematic book for students and teachers in low grades, grades 1-3. Analysis of the data of this research through three stages, namely data condensation, data display, and drawing conclusions or verification. This study found that students' thematic books present higher-order thinking skills at the C4-C6 level referring to the revised Bloom's taxonomy. Student thematic books also present material to foster the ability to reason, think critically / creatively, and reasoning abilities. Meanwhile, the design of learning in the teacher's thematic books to promote higher-order thinking skills uses a scientific learning approach and is student-centred.